Fungsi Pengawasan Pengelolaan Dana Desa Oleh Badan Permusyawaratan Desa di Desa Dewasari Kecamatan Cijeungjing Kabupaten Ciamis - Asep Nurdin Rosihan Anwar; Mico Ariel Wahyu Purnomo; Sabrina Dea Andiyani; Siti Saniaturohmah; Salsabila Dwi Nafisha; Ade Samsa (Lembaga Pengembangan Kinerja Dosen, 2024)
This research is motivated by issues in the implementation of development in Dewasari Village caused by the village's limited budget. However, the Village Consultative Body (BPD) of Dewasari, as the supervisory institution for the Dewasari Village government, has not been optimal in performing its functions, particularly its oversight function. The aim of this study is to understand the management of village funds by the BPD of Dewasari Village, Cijeungjing District, Ciamis Regency. The research method used in this study is descriptive with a qualitative approach. The data collection techniques used by the researchers include literature study and field study, including observation, documentation, and interviews. The data analysis techniques employed are data reduction and data triangulation. The results of the study indicate that the BPD of Dewasari Village has not been optimal in performing its oversight function, as evidenced by several indicators that have not been optimally met, such as the processes of measuring performance, comparing performance with standards, and determining corrective actions. The obstacles faced by the BPD in carrying out the oversight process include the timing of the supervision, lack of understanding and competence of the BPD in supervising the management of village funds, and the limited human resources available to the BPD of Dewasari Village.